Pengaruh Teknik Green Marketing terhadap Loyalitas Konsumen pada Produk Ramah Lingkungan dengan Evaluasi Teknik Penetapan Harga Hijau (Green Pricing) sebagai Variabel Mediasi - Arifin, Indra Welly; Harahap, Hastuti Handayani; Rajagukguk, Frederick Rudy Sentosa (Accounting Progress, 2024)
This research is about the influence of green marketing techniques on consumer loyalty to environmentally friendly products with evaluation of green pricing techniques as a mediating variable. Through data analysis using SMART PLS, this research aims to provide a better understanding of how green marketing can influence consumer loyalty with the help of green pricing as a mediating variable. The first hypothesis is accepted that Green Pricing Techniques (Z) have an effect on Consumer Loyalty (Y). The second hypothesis is accepted that Green Marketing Techniques (X) influence Consumer Loyalty (Y). The third hypothesis is accepted that Green Marketing Techniques (X) influence Green Pricing Techniques (Z). The fourth hypothesis is accepted that Green Marketing Techniques (X) have a significant effect on Consumer Loyalty (Y) through Green Pricing Techniques (Z) as an intervening variable.